2021
DOI: 10.3390/ijerph18126499
|View full text |Cite
|
Sign up to set email alerts
|

Automated Detection and Screening of Traumatic Brain Injury (TBI) Using Computed Tomography Images: A Comprehensive Review and Future Perspectives

Abstract: Traumatic brain injury (TBI) occurs due to the disruption in the normal functioning of the brain by sudden external forces. The primary and secondary injuries due to TBI include intracranial hematoma (ICH), raised intracranial pressure (ICP), and midline shift (MLS), which can result in significant lifetime disabilities and death. Hence, early diagnosis of TBI is crucial to improve patient outcome. Computed tomography (CT) is the preferred modality of choice to assess the severity of TBI. However, manual visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 127 publications
0
24
0
Order By: Relevance
“…From our extensive literature review, it was observed that many of the CAD tools in the area of several medical fields have used accuracy, sensitivity or recall, specificity, positive predictive value (PPV) or precision, F-measure or F-score, and area under the curve (AUC) to evaluate the performance of the system [ 274 , 275 , 276 ]. Similarly, the performance of the CAD tool for the identification of COVID-19 was also evaluated using the same performance parameters as mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…From our extensive literature review, it was observed that many of the CAD tools in the area of several medical fields have used accuracy, sensitivity or recall, specificity, positive predictive value (PPV) or precision, F-measure or F-score, and area under the curve (AUC) to evaluate the performance of the system [ 274 , 275 , 276 ]. Similarly, the performance of the CAD tool for the identification of COVID-19 was also evaluated using the same performance parameters as mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…Machine Learning Techniques ML uses various algorithms for the following key steps: preprocessing and segmentation; feature extraction; dimensionality reduction or feature ranking; and classification. Image preprocessing is a crucial preliminary step as it enhances the image quality or resolution using appropriate filters [74][75][76]. Extraction of the correct region of interest (ROI) is the necessary initial step for coronary plaque detection before further characterization.…”
Section: And DL Techniques In Cadmentioning
confidence: 99%
“…Typically, automated detection systems utilize a combination of image processing techniques, including preprocessing, segmentation, feature extraction, feature selection, and classification. 2 Numerous ML and DL techniques have been employed for detecting and segmenting brain structures to enable volumetric analysis (such as NEUROShield), 11 as well as screening ICH and other related pathologies. [12][13][14][15] Advanced image processing techniques have been devised to detect ICH, potentially enhancing the speed and precision of ICH detection, thereby improving the patients' prognosis.…”
Section: Introductionmentioning
confidence: 99%